Pharmacokinetics and Pharmacodynamics of a Novel Virulent Klebsiella Phage Kp_Pokalde_002 in a Mouse Model - Dhungana, Gunaraj; Nepal, Roshan; Regmi, Madhav; Malla, Rajani (Frontiers in Cellular and Infection Microbiology, 2021)
Phage therapy is considered one of the most promising alternatives to antibiotics as we face a global antibiotic resistance crisis. However, the pharmacokinetics (PK) and pharmacodynamics (PD) of phage therapy are largely unknown. In the present study, we aimed to evaluate the PK/PD of a locally isolated virulent novel øKp_Pokalde_002 (Podoviridae, C1 morphotype) that infects carbapenem-resistant Klebsiella pneumoniae (Kp56) using oral and intraperitoneal (IP) route in a mouse model. The result showed that the øKp_Pokalde_002 rapidly distributed into the systemic circulation within an hour via both oral and IP routes. A higher concentration of phage in plasma was found after 4 hrs (2.3x105 PFU/mL) and 8 hrs (7.3x104 PFU/mL) of administration through IP and oral route, respectively. The phage titer significantly decreased in the blood and other tissues, liver, kidneys and spleen after 24 hrs and completely cleared after 72 hrs of administration. In the Kp56 infection model, the bacterial count significantly decreased in the blood and other organs by 4-7 log10 CFU/mL after 24 hrs of øKp_Pokalde_002 administration. The elimination half-life of øKp_Pokalde_002 was relatively shorter in presence of host-bacteria Kp56 compared to phage only suggesting rapid clearance of phage in presence of a susceptible host. Further, administration of the øKp_Pokalde_002 alone in healthy mice (via IP or oral) did not elicit stimulate any notable pro-inflammatory cytokines (TNF-α and IL-6)to the tissues. Also, treatment with øKp_Pokalde_002 resulted in a significant reduction of pro-inflammatory cytokines (TNF-α and IL-6) caused by bacterial infection thereby reducing the tissue inflammation. In conclusion, the øKp_Pokalde_002 possesses good PK/PD properties and can be considered as a potential therapeutic candidate for future phage therapy in carbapenem-resistant K. pneumoniae infections.